Peran pancasila sebagai dasar identitas nasional indonesia - dalimunthe, fitri romaito (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the role of Pancasila as the foundation of Indonesia’s national identity in facing the dynamics of globalization. Globalization, characterized by the rapid advancement of information technology and the influx of foreign cultures, has had a significant impact on people’s lives, particularly through the erosion of nationalist values ​​and moral degradation. This study uses a qualitative approach through library research, analyzing various relevant scientific sources. The results show that Pancasila holds a strategic position as a state ideology, way of life, and national identity, functioning as a filtering mechanism against the negative influences of globalization. However, the application of Pancasila values ​​in social life, especially among the younger generation, still faces various obstacles, such as declining patriotism, the influence of digital media, and a moral crisis. Therefore, strategies are needed to strengthen and revitalize Pancasila values ​​through education, digital literacy, and active government and community involvement. Thus, Pancasila remains relevant as the main foundation in maintaining national identity amidst global fluctuations.